Reduction in FSH Throughout the Menstrual Cycle After Omega-3 Fatty Acid Supplementation in Young Normal Weight but not Obese Women. (August 2019) - Bauer, Jessica L.; Kuhn, Katherine; Bradford, Andrew P.; Al-Safi, Zain A.; Harris, Mary A.; Eckel, Robert H.; Robledo, Celeste Y.; Malkhasyan, Anahit; Johnson, Joshua; Gee, Nancy R.; Polotsky, Alex J.
Dietary fish oil restores ovarian function in subfertile rats, which is thought to be associated with decreased transcription of follicle-stimulating hormone (FSH) β-subunit. We have previously demonstrated a reduction in early follicular serum FSH levels in normal weight but not obese women after treatment with omega-3 polyunsaturated fatty acids (PUFA). Herein, we report the effect of supplementation with omega-3 PUFA on urinary reproductive hormones across the whole menstrual cycle. This interventional study included 17 eumenorrheic women, aged 24-41 years. One month of daily morning urine was collected before and after 1 month of omega-3 PUFA supplementation with 4 g of eicosapentaenoic acid and docosahexaenoic acid daily. Measurements included urinary FSH, luteinizing hormone (LH) and estrogen and progesterone metabolites, plasma fatty acid composition, and markers of endoplasmic reticulum stress. Compliance with dietary supplementation was verified by significantly reduced ratios of omega-6 to omega-3 PUFA for all subjects after treatment ( P < .01). After 1 month of omega-3 PUFA supplementation, urinary FSH was significantly decreased in normal weight, but not obese women, in both follicular and luteal phases (−28.4% and −12.6%, respectively, both P = .04). No significant changes were seen in LH or sex steroids for either weight group. The selective and specific decrease in FSH suggests that omega-3 PUFA supplementation merits further investigation in normal weight women with decreased fertility and/or diminished ovarian reserve.